Examining Perceived Organizational Support, Work-Life Balance, and Role Breadth Self-Efficacy in Predicting Employee Adaptive Performance - Emur, Alvin Permana; Satrya, Aryana (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: The study's purpose is to investigate the effect of perceived organizational support (POS) and work-life balance (WLB) on adaptive performance and examine the role of role breadth self-efficacy (RBSE) as mediation in the proposed research model. Design/Methods/Approach: This study adopts a quantitative approach by distributing cross-sectional surveys of multi-sector employees. The collected data were assessed for model evaluation and structural equation model with SmartPLS 4 and tested with disjoint two-stage approach techniques. The study sample was collected from 230 respondents across various industrial sectors. Findings: The results indicate that perceived organizational support and work-life balance have a positive direct effect on adaptive performance and a positive indirect effect through RBSE mediation. Originality: This study makes several contributions to the literature on RBSE and adaptive performance, which has yet to be extensively proposed. Additionally, testing the indirect influence of POS and WLB on adaptive performance through RBSE, an area that has yet to be widely studied, emphasizes the prominent capabilities of RBSE as a mediator. Practical/Policy Implications: This study suggests the importance of strategy and planning for organizations in the aspect of human resources to pay attention to expanding and broadening employee roles, which is key in improving adaptive performance. Then, the findings of this study can be a reference for various business organizations to raise concerns about WLB initiatives and interventions and consideration to improve organizational support for employee work effectiveness.